2021
DOI: 10.24940/theijbm/2021/v9/i2/bm2102-036
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Financial Inclusion on Performance of Microfinance Banks in Kenya

Abstract: Financial inclusion brings closer financial services at affordable costs to sections of disadvantaged and low-income segments of society. There have been many formidable challenges in financial inclusion such challenges include; bridging the gap between the sections of society that are financially excluded within the ambit of the formal financial system, providing financial literacy and strengthening credit delivery mechanisms so as to promote financial economic growth. A nation can grow economically and socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(15 reference statements)
1
2
0
Order By: Relevance
“…It is shown that access to third party funds can improve performance which is reflected in the growth of credit volume, profit growth, asset growth and customer growth. The findings of this study reinforce previous findings which found that financial inclusion was found to be able to improve performance (Oranga & Ondabu, 2018, financial inclusion had a positive effect on performance (Issaias et al, 2021;History et al, 2020;Sanistasya et al , 2019).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…It is shown that access to third party funds can improve performance which is reflected in the growth of credit volume, profit growth, asset growth and customer growth. The findings of this study reinforce previous findings which found that financial inclusion was found to be able to improve performance (Oranga & Ondabu, 2018, financial inclusion had a positive effect on performance (Issaias et al, 2021;History et al, 2020;Sanistasya et al , 2019).…”
Section: Resultssupporting
confidence: 90%
“…'The Financial Inclusion Program provides opportunities for accessing credit and savings safely, and can avoid dependence on economically disadvantaged communities from informal credit sources that have high risks such as moneylenders (Sarma, 2010). Financial inclusion was found to be able to improve performance (Bongomin et al, 2017), (Oranga & Ondabu , 2018), and financial inclusion has found a positive effect on performance (Sanistas yes et al, 2019;History et al, 2020;Issaias et al, 2021), Based on this, the hypothesis is formulated as follows, H4: Financial inclusion has a positive effect on sustainable performance.…”
Section: Introductionmentioning
confidence: 99%
“…Although micro-financing is crucial for strengthening the poor's capacity, it is still challenged by the problem of inaccessibility among the people who need it in Kenya. While micro-finance institutions operate deposit, lending, and insurance activities they have not managed to exhaust the need for all SMEs in Kenya (Issaias et al, 2021). In addition to the problem of in exhaustive capacity to meet the needs of SMEs in Kenya, microfinance institutions have witnessed a drop in their performance over the years (Muithya et al, 2020;Kahihu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%